Hyperuricemia in ob/ob mice relates to hepatocellular pyruvate metabolism/ xanthine oxidase axis - Shan Zhang; Shasha Hu; Haibo Tan; Ertao Jia (PLoS ONE, 2025)
Objective The study aimed to examine the association between obesity and hyperuricemia in ob/ob mice. Methods An animal model of obesity was developed using male ob/ob mice. Biochemical parameter test kits were used to measure serum uric acid (UA), hepatic xanthine oxidase (XOD) activity, serum creatinine (Scr), serum lipid profiles, and blood urea nitrogen (BUN). Then, liver tissues were collected for hematoxylin and eosin (H&E) staining, flow cytometry, and western blot (WB) analysis. Furthermore, Huh-7 cells were co-cultured with THP-1 macrophages for 24 hours, with or without LPS + IFN-γ or PA, and subsequently analyzed for XOD activity. In addition, the Huh-7 cells stimulated with PA were analyzed by metabolomics and validated by WB and RT-qPCR. Results Levels of Serum lipid profiles, UA, and XOD activity are elevated in ob/ob mice. In ob/ob mice, liver M1 macrophage polarization is markedly enhanced. In vitro studies show that elevated XOD activity in hepatocytes during hyperlipidemia does not correlate with M1 macrophage polarization. Metabolomics showed that the XOD activity of hepatocytes in hyperlipidemia may be related to pyruvate metabolism. Moreover, the protein and mRNA levels of pyruvate dehydrogenase (PDH), an enzyme that limits pyruvate accumulation, were significantly down-regulated in Huh-7 cells with PA stimulation. Conclusion Hyperuricemia in ob/ob mice relates to hepatocellular pyruvate metabolism/ xanthine oxidase axis.